Multi-Level Governance As A Climate Change Adaptation Strategy In The Coastal Cities In Indonesia And Thailand - Andi Luhur Prianto; Abdillah Abdillah; Arifeen Yama (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
Multi-level global governance, or MLG, is now a framework for reducing the effects of climate change on a worldwide scale. The systemic and architectural aspects of multi-level global climate governance across many levels and sectors are examined in this article. Models and their real-world application at the international, regional, national, provincial, and city/district levels are discussed. Exploratory qualitative research employing a multi-case study technique is the methodology employed, with a focus on Bangkok, Thailand, and Samarang City, Indonesia. The data analysis technique uses the Nvivo-12 version of the tool. The findings demonstrated the following: (1) the multilevel climate governance system on climate change adaptation in coastal areas can be viewed as a structure that offers opportunities for policy innovation-based climate strategies; (2) each level of the global adaptation system has distinct roles, difficulties, opportunities, and ways to offer insights or conclusions as recommendations for policy; (3) the primary takeaway is that the MLG adaptation system is more controllable and scalable for mitigating climate change; and (4) the multi-sector and multi-actor system structure offers chances to rally diverse interests in support of climate policy objectives. This research contributes to improving the adaptation of vulnerable systems, policies and communities at all levels to the threat of climate change in two countries, Indonesia and Indonesia.